Volume 2C: Turbomachinery 2016
DOI: 10.1115/gt2016-56659
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Flow in the Row Labyrinth Seal of an Axial Turbine Using a Low-Mach Preconditioning Technique

Abstract: Labyrinth seals on shrouded blades are an effective way for reducing efficiency penalties, as compared to free ended blades. Due to the difficulties of gaining optical access to cavity regions, mostly pressure measurements are available in the literature, from which the details of the flow must be inferred. The use of numerical tools can provide insight in the flow topology and therefore help obtaining a better understanding of the factors (geometric, thermodynamic and aerodynamic) which can affect the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Liu [17] concluded that the LS arranged on the top of the shroud can significantly reduce the total pressure loss. Flow characteristics of LS on an axial-flow turbine were investigated with low Mach number preconditioning technique by Jens [18]. Krzysztof [19] developed a type of cavity seal and greatly reduced the aerodynamic force of LS under small clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [17] concluded that the LS arranged on the top of the shroud can significantly reduce the total pressure loss. Flow characteristics of LS on an axial-flow turbine were investigated with low Mach number preconditioning technique by Jens [18]. Krzysztof [19] developed a type of cavity seal and greatly reduced the aerodynamic force of LS under small clearance.…”
Section: Introductionmentioning
confidence: 99%